One-pot synthesis of manganese oxide/graphene composites via a plasma-enhanced electrochemical exfoliation process for supercapacitors. (9th June 2020) - Dang, Minh Nhat; Nguyen, Thanh Hai; Nguyen, To Van; Thu, Tran Viet; Le, Hoang; Akabori, Masashi; Ito, Nobuaki; Nguyen, Hai Yen; Le, Trong Lu; Nguyen, Tuan Hong; Nguyen, Van Thao; Phan, Ngoc Hong
Abstract: In this work, a feasible one-pot approach to synthesize manganese oxide/graphene composites, the so-called plasma-enhanced electrochemical exfoliation process (PE 3 P), has been developed. Herein, a composite of graphene decorated with manganese oxide nanoparticles was prepared via PE 3 P from a KMnO4 solution and graphite electrode under a voltage of 70 V in an ambient environment. By controlling the initial KMnO4 concentration, we obtained distinct MnO2 /graphene samples. The prepared samples were characterized by scanning electron microscopy, transmission electron microscopy, x-ray diffraction, x-ray photoelectron spectroscopy, and Raman spectroscopy. The electrochemical measurements of the MnO2 /graphene composites revealed that the specific capacitance of the samples is approximately 320 F g –1 at a scan rate of 10 mV s –1, which is comparably very high for manganese oxide/carbon-based supercapacitor electrode materials. Considering the simple, low-cost, one-step and environmentally friendly preparation, our approach has the potential to be used for the fabrication of MnO2 /graphene composites as the electrode materials of supercapacitors.